2014
DOI: 10.1371/journal.pone.0088129
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Energy Micro-CT Functional Imaging of Primary Lung Cancer in Mice Using Gold and Iodine Nanoparticle Contrast Agents: A Validation Study

Abstract: PurposeTo provide additional functional information for tumor characterization, we investigated the use of dual-energy computed tomography for imaging murine lung tumors. Tumor blood volume and vascular permeability were quantified using gold and iodine nanoparticles. This approach was compared with a single contrast agent/single-energy CT method. Ex vivo validation studies were performed to demonstrate the accuracy of in vivo contrast agent quantification by CT.MethodsPrimary lung tumors were generated in LSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 45 publications
1
82
0
Order By: Relevance
“…7 Based on the k-edge, which is specific for the used substance, the contrast can be increased. Multimodal imaging is possible when several k-edge substances are used.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Based on the k-edge, which is specific for the used substance, the contrast can be increased. Multimodal imaging is possible when several k-edge substances are used.…”
Section: 22mentioning
confidence: 99%
“…4,5 Due to the relatively high costs of gold, alternative materials, such as iodine, platinum, ytterbium, bismuth, and tantalum, are presently investigated in preclinical studies, 6 and iodine has been tested as a contrast agent in lung cancer patients. 7 For radiation therapy and for surgical removal of tumors in the brain, it is key to know the exact localization and size of a tumor. Tumor imaging with nanoparticles can be improved by coupling them…”
Section: Introductionmentioning
confidence: 99%
“…10 Consequently, the injection of contrast agents is necessary to achieve accurate and abundant information of region of interest. 11 Iodinated compounds are widely used as CT contrast agents in clinical applications due to their prominent photoelectric effect. 12 The cube of the high atomic number (Z=53) endows iodine with favorable X-ray attenuation property through photoelectric effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ashton et al demonstrated tumor accumulation of PEGylated AuNP in an interesting study using dual-energy CT. AuNP were injected and allowed to accumulate in tumors for 2 days before the injection of iodine nanoparticles. The iodine particles acted as blood pool CA, while the AuNP provided contrast within the tumors [91]. PEGylated hollow AuNP are also capable of targeting tumors passively as shown by Park et al After injection into the tail vein, particle location was assessed using CT imaging and inductively coupled plasma (ICP) mass spectroscopy.…”
Section: Passively Targeted Gold Nanoparticle Formulationsmentioning
confidence: 99%